Optimization of Used Cooking Oil Utilization through Aromatherapy Candle-Making Training: A Case Study in Lestari Jaya Hamlet, East Kutai, East Kalimantan: Optimalisasi Pemanfaatan Minyak Jelantah melalui Pelatihan Pembuatan Lilin Aromaterapi: Studi Kasus di Dusun Lestari Jaya, Kutai Timur, Kalimantan Timur - Aulia Almag Fira; Muhammad Rizqy Septyandy; Angelia Cristin; Pedrico Partogi Manullang; Nadia Putri Alfiani; Muftia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2026)
Used cooking oil is a domestic waste frequently disposed of improperly, causing persistent pollution to water and soil. An aromatherapy candle-making training program based on recycled used cooking oil was conducted in Lestari Jaya Hamlet, Kutai Timur Regency, aiming to optimize waste utilization, reduce environmental contamination risk, and promote the development of creative, eco-friendly businesses within the community. The event engaged 16 participants from the PKK women's group and local residents through material presentations and hands-on practice. The success of the program was evaluated using a Likertscale questionnaire. Results revealed a mean satisfaction score of 4.4, indicating a high level of satisfaction with the training received. Financial analysis showed total monthly production costs of Rp6,569,038.89 for 1,000 candle units, with a selling price set at Rp8,500.00 per unit and a benefit-cost ratio (R/C) of 1.3, reflecting business feasibility and real profit potential. This initiative effectively enhanced environmental awareness, entrepreneurial skills, and motivated the community to manage domestic waste productively. The main recommendation is to replicate this training model in other areas and to integrate digital marketing strategies to foster sustainable development of micro-businesses based on waste materials.